Analisis Unsur Visual Karya Kolase Tema Transportasi Kelas I SDN Karangrejo 02 Semarang - Sabandini, Anggi Arum; Fajriyah, Khusnul; Mushafanah, Qoriati (YASIN, 2023)
At the elementary school education level, which is generally children aged 6-12 years, learning activities that produce works of art have an impact on student learning progress, one of which is making collage art. Grade 1 students are often interested in and exposed to various types of transportation, such as land, water and air transportation. Therefore, choosing transportation images as the theme of the collage can provide direct relevance to their lives. The purpose of this study was to find out the visual elements of a transportation theme collage made by first grade students at SDN Karangrejo 02 Semarang. This study uses Qualitative Research, because researchers observe, analyze, and interpret an object to be examined using interview, observation and documentation methods. Test the validity of the data using a triangulation technique that is used to test the credibility of the data. The results of the research carried out were that the results of the collage work of class I students at SDN Karangrejo 02 Semarang totaling sixteen students with pictures of transportation equipment made of paper, the results of the student collage work were many who were good at making collages, but there were still students who were not neat in pasting, there are still many students who miss the drawing line. Some students may not have fully mastered their fine motor skills, so they have difficulty controlling their hand movements precisely. So with that it is very important to provide proper guidance and training to students through repetition of exercises and supportive approaches, students can improve their skills in pasting pictures neatly.